Utilizing Solar Power Plants as Renewable Energy for the Future: (Case Study: PLTS Likupang) - Enzza Sampaleng; Deitje S. Pongoh; Muchdar Daeng Patabo; Benaya Ticoalu; Einstein Kondoj; Gabriel Rumagit; Timothy Mamentu; Felove Mirah; Mikha Assa (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
Solar energy is one of the renewable energy sources that has great potential to replace conventional energy sources that have a negative impact on the environment. Solar power plants (PLTS) are technologies that utilize solar energy to generate electricity by converting sunlight into electric current. PLTS can be divided into two types, namely photovoltaic (PV) and concentration (CSP). PV is a PLTS that uses solar cells to directly convert sunlight into electricity, while CSP is a PLTS that uses mirrors or lenses to focus sunlight to a point and generate heat that is used to drive turbines. Both types of PLTS have their own advantages and disadvantages, depending on factors such as location, climate, cost, and land availability. This study discusses the development, challenges, and prospects of PLTS as a renewable energy source for the future. This study also provides an example of Likupang PLTS in North Sulawesi, which is one of the largest PLTS in Indonesia. It can supply electricity to several regions around it with an installed capacity of 21 MWp. This study shows that PLTS has economic, social, and environmental benefits and can contribute to achieving national and global renewable energy targets.